2020
DOI: 10.2147/ccid.s271013
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Study to Evaluate the Efficacy and Safety of a Hair Serum Product in Healthy Adult Male and Female Volunteers with Hair Fall</p>

Abstract: Background: Hair fall is a widespread problem among all genders, ages, and ethnicity with both physical and psychological effects. Objective: This clinical study was designed to evaluate the efficacy and safety of a hair serum formulation containing amla extract, freeze-dried coconut water, and the micronutrient selenium along with sandalwood odorant and peanut shell extract in healthy male and female volunteers with hair fall. Methods: A total of 42 subjects were enrolled and completed the study and they used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Its chemical constituents contain tetranor terpenoid lactones azadirachtin, nimbin, nimbidin, salanin, and nimbolin-B. Neem oil additionally incorporates nimbolides, oli chinolide-B, and azadiradione [ 56 , 83 ]. It is commonly used for treatment of dandruff, because it produces antifungal, antibacterial, and ache-relieving compounds that treated and ruff [ 56 ].…”
Section: Hair Cosmetic Containing Herbalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its chemical constituents contain tetranor terpenoid lactones azadirachtin, nimbin, nimbidin, salanin, and nimbolin-B. Neem oil additionally incorporates nimbolides, oli chinolide-B, and azadiradione [ 56 , 83 ]. It is commonly used for treatment of dandruff, because it produces antifungal, antibacterial, and ache-relieving compounds that treated and ruff [ 56 ].…”
Section: Hair Cosmetic Containing Herbalsmentioning
confidence: 99%
“…It contains tetranor, terpenoid, lactones azadirachtin, nimbin, nimbidin, salanin, and nimbolin-B. Neem oil additionally includesnimbolides, olichinolide-B, and azadiradione [ 56 , 83 ]. Its antibacterial of neem prevent gingivitis, and it is also used to prevent cavities and prevent bad breath [ 56 ].…”
Section: Oral Hygiene Productmentioning
confidence: 99%
“…The compounds of low molecular weight can penetrate the hair and improve the mechanical properties of the cortex, while high molecular weight compounds can protect the hair and prevent degradation. Majeed et al (2020) reported that coconut water increased hair density and growth in male and female volunteers, and reduced itching sensitivity [138]. Coconut water, which contains flavonoid compounds, may protect the hair follicles.…”
Section: Hair Cosmeticsmentioning
confidence: 99%
“…Sweet Potato (Ipomoea batatas), [8][9][10] Snake Gourd (Trichosanthes Anguina L), 4,[11][12][13] False Daisy (Eclipta prostrata), [14][15][16] Curry Leaves (Murraya koenigii), [17][18][19] Indian Gooseberry (Phyllanthus emblica), [20][21][22] Almond (Prunus dulcis), 23,24 Walnut (Juglans regia), 24 Groundnut (Arachis hypogaea), 25 Flaxseed (Linum usitatissimum), [26][27][28] Chia Seed (Salvia hispanica), 29,30 Lemon (Citrus x limon), [31][32][33] Chickpea (Cicer arietinum), 34 Cinnamon (Cinnamomum Zeylanicum Blume), 35,36 Guava (Psidium guajava), [37][38][39] Cumin (Cumin cyminum), 40,41 Spinach (Spinacia oleracea). 42…”
Section: Test Productmentioning
confidence: 99%